PROXEMES AS MARKERS OF NON-VERBAL CODE IN FICTION TEXT (ON THE MATERIAL OF DYSTOPIAN NOVEL “BRAVE NEW WORLD” BY A. HUXLEY) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-50-59This article is devoted to peculiarities of non-verbal code of communication on the example of proxemes. The author provides the classification (personified and non-personified models) and the typology of proxemes, identifies the specifical usage of proxemes in the novel “Brave New World” and highlights the frequency of each of the proxemes in architectonics of the novel. The role of proxemes in transmitting non-verbal information in fictional world of the novel by A. Huxley.Key words: literary text, markers of non-verbal code, proxemes, personalized proxemes, nonpersonalized proxemes